2014
DOI: 10.5056/jnm.20.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nerve Regulation of Colonic Peristalsis in Guinea Pigs

Abstract: Background/AimsColonic peristalsis is mainly regulated via intrinsic neurons in guinea pigs. However, autonomic regulation of colonic motility is poorly understood. We explored a guinea pig model for the study of extrinsic nerve effects on the distal colon. MethodsGuinea pigs were sacrificed, their distal colons isolated, preserving pelvic nerves (PN) and inferior mesenteric ganglia (IMG), and placed in a tissue bath. Fecal pellet propagation was conducted during PN and IMG stimulation at 10 Hz, 0.5 ms and 5 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…The inhibitory effects of noradrenaline were mediated by the α 2 ‐adrenergic receptors as demonstrated by the effects of α 2 ‐adrenergic receptor blocker, yohimbine. An involvement of α 2 ‐adrenergic receptors has also been demonstrated for peristaltic activity in the mouse and guinea pig . A role for the β‐adrenergic receptor through the beta‐blocker propranolol was not found.…”
Section: Discussionmentioning
confidence: 98%
“…The inhibitory effects of noradrenaline were mediated by the α 2 ‐adrenergic receptors as demonstrated by the effects of α 2 ‐adrenergic receptor blocker, yohimbine. An involvement of α 2 ‐adrenergic receptors has also been demonstrated for peristaltic activity in the mouse and guinea pig . A role for the β‐adrenergic receptor through the beta‐blocker propranolol was not found.…”
Section: Discussionmentioning
confidence: 98%
“…This variety suggests a relatively autonomic nervous system in the gut wall [25]. Although the stimulatory effects of pelvic nerve stimulation and inhibitory effects of inferior mesenteric ganglia could not be excluded from the regulation of colonic motility (guineapig distal colon [11], the neural mechanisms underlying the colonic motor patterns have now and do not require inputs from the mucosa or submucosal ganglia for their generation [25]. We found that under local electrical stimulation the LM responded with contraction, while the response of CM consisted of an initial relaxation followed by contraction.…”
Section: Discussionmentioning
confidence: 99%
“…In rat colon, the LM contracted and relaxed in a fashion reverse to that of the CM during the in the murine large intestine could be triggered by longitudinal stretch [9], while the ascending excitatory and descending inhibitory neural pathways in guinea pig distal colon depend on sensory elements within the CM layer [10]. In rat colon, an essential role in ascending Obviously, although that knowledge the colon motility has advanced during the last years, the autonomic regulation of colonic motility and the mechanisms underlying ascending and descending neuromuscular communications are still not fully understood [11,12] and require further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic input reduces colonic smooth muscle contractility (Garry & Gillespie, 1955; Gillespie, 1962; Mackenna & McKirdy, 1972). Distension‐evoked phasic contractions and the speed of pellet propulsion in guinea pig distal colon can be significantly reduced by sympathetic input via an α 2 receptor‐dependent mechanism (Crema et al, 1970) (Gribovskaja‐Rupp et al, 2014), likely to involve inhibition of both ascending and descending cholinergic neurotransmission in the myenteric plexus (Spencer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%